Managers self-efficiency and its effect on Exhaustion at the public schools, Iran - Mehrad, Aida (Universitas Ahmad Dahlan, 2014)
AbstractOne of the threaten behavior among managers is exhaustion. In fact, exhaustion assumed as a state of physical and emotional tiredness that appear in interaction with employees and students during working hours at school. The existence of this irregular feeling leads to low level of presentation at school and generates in adequate outcomes. Furthermore, recognizing and applying the optimistic factors such as self-efficiency can be valuable motivator in controlling and reducing the amount of abnormal reactions such as exhaustion among managers at schools. The purpose of current study is focused on association between managersâ self-efficiency and exhaustion at public schools in Tehran, Iran. The results demonstrated that self-efficiency predicts the amount of exhaustion among managers and there is negative association between exhaustion and selfâefficiency at school. Besides, the present paper supports the impact of efficiency on the amount of exhaustion among schools managers and reduction this unsatisfactory phenomenon at schools.Keywords: Managers, Self-efficacy; Exhaustion, Schools